Paylater usage experience among State Islamic University students: Key factors - Siti Amaroh; Husnurrosyidah Husnurrosyidah; Amelia Wulandari (Faculty of Islamic Economics and Business, UIN Salatiga, 2025)
This study examines the effect of financial behavior, perceived usefulness, and Islamic values on Paylater usage experience, with locus of control as a mediating variable. A quantitative approach was employed, and 208 students at the State Islamic Universities in Central Java as respondents. Data were analyzed using Partial Least Squares Structural Equation Modelling. The results indicate that financial behavior negatively affects Paylater usage experience, whereas perceived usefulness has a positive effect. Islamic values positively influence locus of control and negatively affect Paylater usage experience, while financial behavior also positively influences locus of control. However, perceived usefulness does not affect locus of control, and locus of control neither influences Paylater usage experience nor mediates the relationship between financial behavior, perceived usefulness, and Islamic values on Paylater usage experience. The findings imply that Islamic universities should strengthen financial literacy, Islamic financial ethics, and consumer education to promote responsible use of digital credit services among students